2019
DOI: 10.4022/jafib.2200
|View full text |Cite
|
Sign up to set email alerts
|

4D Volume Intracardiac Echocardiography for Intraprocedural Guidance of Transcatheter Left Atrial Appendage Closure

Abstract: The primary drawback of the previous generation of 4D ICE

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Guidance of LAAC with 3D-ICE catheters is feasible, with comparable LAA sizing to 3D-TEE and CCTA. 26,27 Newer low-profile 3D catheters with a broader angle of visualization, standardized workflow, and preprocedural CCTA LAA sizing and planning will…”
Section: Despite the Growing Number Of Laac Procedures In The Unitedmentioning
confidence: 99%
“…Guidance of LAAC with 3D-ICE catheters is feasible, with comparable LAA sizing to 3D-TEE and CCTA. 26,27 Newer low-profile 3D catheters with a broader angle of visualization, standardized workflow, and preprocedural CCTA LAA sizing and planning will…”
Section: Despite the Growing Number Of Laac Procedures In The Unitedmentioning
confidence: 99%
“…Four‐dimensional (4D)‐ICE (real‐time 3D technology) catheters have been introduced as a more novel interventional imaging technique, which has a broader imaging field. It can realize the multi‐plane reconstruction of LAA anatomical structure, allow real‐time observation of the intracardiac structure and blood flow, and provide high‐quality real‐time 3D images 43–45 . Small sample studies have found that 4D‐ICE‐guided LAAC is safe and feasible 45 .…”
Section: The Future Is Promising For Ice‐guided Laacmentioning
confidence: 99%
“…A 14 Fr ICE catheter used in the right atrium only has seen early promise and comparable results to TEE, however the real benefit of ICE over TEE lies in the proximity of the ultrasound transducer to the anatomy of interest, the LAA ostium 3 . This allows higher resolution assessment of the device from the tip of the LAA‐LSPV ridge, or from within the adjacent left sided pulmonary veins.…”
Section: Figurementioning
confidence: 99%